EDUCATIONAL DIMENSIONS OF FATWA IN ISLAMIC LEGAL LITERACY: STUDY OF EAST JAVA MUI FATWA NUMBER 1 OF 2025 CONCERNING SOUND HOREG - Lintang Ramadhani; Rofianti Anggraini; Riavita Maghfiroh; Muhammad Sahal Malik Fajar; Hilya Adilah (STKIP Pesisir Selatan, 2026)
Objective: This research aims to analyze the educational dimensions in the Fatwa of MUI of East Java concerning the Use of Sound Horeg and its contribution in strengthening Islamic legal literacy. Methods: The research uses a qualitative approach with a type of normative legal research through a conceptual and case approach. Data was obtained through a documentation study of the East Java MUI Fatwa Number 1 of 2025, supported by various scientific literature regarding fatwas and Islamic legal education. The analysis was carried out descriptively-analytically on the legal arguments and educational values ​​contained in the fatwa. Results: The findings reveal that; (1)The educational dimension is reflected in its explanation of the istinbāṭ from Qur'an, hadith, uṣūl al-fiqh, maqāṣid al-syarī'ah to knowing the legal ruling but also the reasoning behind it. Furthermore,(2)the fatwa promotes contextual Islamic legal literacy by fostering critical understanding of contemporary legal issues while internalizing the values of public welfare, social responsibility, and harm prevention. Novelty: This study offers a new perspective by examining the East Java MUI Fatwa from an educational perspective rather than merely as a product of Islamic legal reasoning.